Konsep Zen tentang Pikiran - Setyoakhmadi, Kardono; Nusyirawan, Nusyirawan (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2003)
This is a literary study. All the data used in this study come mainly from biblographical sources. This study is intended to comprehend Zen's conception of mind descriptively, focusing particulary on the writing of its adherents. Since various propositions in Zen-Budhisim is often confusing for many scholars, it is this study's intention to futher examine why this is so.It will be argued in this study that there is a fundamental difference between Chinese and Westren people in terms of their ways of thinking and their sciencetific paradigms that is presumably rooted in their epistemological traditions. In addition, it is widely known that Zen-Budhism was meant to undermine the psychological trap of Westren logis-the same logic that we sometimes used in Indonesia.However, Zen-Budhism is seeking towards liberation, and it is also emphasizing the characters of mind as spontaneous and natural. For Zen-Budhism, it is impossible to be liberated if our mind is not spontaneous and natural